2010
DOI: 10.1002/clen.201000125
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Amaranth Dye onto Alumina Reinforced Polystyrene

Abstract: Adsorptive removal of toxic amaranth dye by alumina reinforced polystyrene (ARP) composite was studied as a function of contact time, pH, initial dye concentration, and temperature. The results indicated that adsorption was strongly dependent on pH and temperature of the dye solution. The adsorption was favored at low pH with the maximum removal at pH 2.0. Langmuir, Freundlich, Temkin, and DubininRadushkevich (D-R) models were used for the description of adsorption equilibrium data and the best interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 43 publications
(45 reference statements)
4
62
1
Order By: Relevance
“…It should be noted that anionic amaranth dye forms strong complexes with positively charged compounds through electrostatic interactions (Tunc and Duman, 2007). Contrariwise, the decrease in AD biosorption capacity observed at higher pH values responds to a less positive charge of the LEC surface, which generates stronger electrostatic repulsion towards AD molecules (Ahmad and Kumar, 2011).…”
Section: Influence Of Solution Ph Levels On Ad Biosorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that anionic amaranth dye forms strong complexes with positively charged compounds through electrostatic interactions (Tunc and Duman, 2007). Contrariwise, the decrease in AD biosorption capacity observed at higher pH values responds to a less positive charge of the LEC surface, which generates stronger electrostatic repulsion towards AD molecules (Ahmad and Kumar, 2011).…”
Section: Influence Of Solution Ph Levels On Ad Biosorptionmentioning
confidence: 99%
“…Furthermore, treatment of azo dyes-containing waters with aerobic microbes does not successfully degrade most dyes, and anaerobic microbial degradation produces by-products such as aromatic amines, which are more toxic, mutagenic and carcinogenic than the dyes themselves (Ahmad and Kumar, 2011). In this context, biosorption may be a desirable alternative because its operation is simple, low cost, reliable and effective and does not produce by-products.…”
Section: Introductionmentioning
confidence: 97%
“…Elucidation of adsorption behavior can be detected from desorption studies 31 and the percentage of desorption is shown in Table 4. The fact that not all Pb(II) ions could be desorbed from the XRL surface suggests that chemical adsorption was involved during the Pb(II) adsorption process.…”
Section: Desorption Studiesmentioning
confidence: 99%
“…Therefore, the CDC-A with the high concentration of phenol groups and a certain amount of anhydride groups also exhibits better adsorption performance than original CDC. Generally, the attraction between adsorbate and adsorbent arises from some of forces listed below: van der Waals forces (4-10 kJ/mol), hydrophobic bond forces (5 kJ/mol), hydrogen bond forces (2-40 kJ/mol), coordination exchange (40 kJ/mol), dipole bond forces (2-29 kJ/mol), and chemical bond forces (>60 kJ/mol) [57,58]. In this study, the adsorption energies ranged from À10.79 to À39.95 kJ/mol.…”
Section: Calculation Resultsmentioning
confidence: 99%